2020
DOI: 10.3390/electronics9122011
|View full text |Cite
|
Sign up to set email alerts
|

V2I Propagation Loss Predictions in Simplified Urban Environment: A Two-Way Parabolic Equation Approach

Abstract: This study is devoted to radio wave propagation modeling in the urban environment. Special attention has been paid to the features of vehicular ad hoc networks (VANETs) and vehicle-to-infrastructure (V2I) communications. For the first time, the three-dimensional bidirectional parabolic equation (PE) method has been applied to the specified problem. Buildings and other obstacles are modeled by impenetrable (perfectly electric conducting) cuboids. A harmonic radiation source with an arbitrary direction pattern m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Knife-edge and PE approaches are the closest related to O-FDTD. However, such methods are limited in the number of wave reflections [36,37] and thus usually limited to a few knife edges or simplified models [45,66]. Multiple knife-edge diffraction [35] solves this issue but is still limited to simple geometries, which renders it unsuited for complex real-world building arrangements.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Knife-edge and PE approaches are the closest related to O-FDTD. However, such methods are limited in the number of wave reflections [36,37] and thus usually limited to a few knife edges or simplified models [45,66]. Multiple knife-edge diffraction [35] solves this issue but is still limited to simple geometries, which renders it unsuited for complex real-world building arrangements.…”
Section: Discussionmentioning
confidence: 99%
“…This rules out the usage of simpler ray-based algorithms that do not take diffraction into account. Knife-edge methods such as the two-way PE [45] consider diffraction, but its application to complex real-world building geometries is challenging. The ITM is likely the most thorough method.…”
Section: Related Workmentioning
confidence: 99%
“…In [10], a failure detector of VANET systems is proposed, which has some notions of signal attenuation. In [11], numerical simulations were performed in various radio-propagation scenarios, where it was shown that various factors affect the attenuation of a signal. A signal tends to attenuate over large distances in line-of-sight (LOS) contexts, whereas in non-line-of-sight (NLOS) contexts, the presence of a building or obstacle can greatly affect signal intensity (in dBm).…”
Section: Anomaly Detectionmentioning
confidence: 99%